CFD analyses of the wind drags on khaya senegalensis and eugenia grandis - Li, Yangyang (2019)
The drag coefficients of one mature Khaya Senegalensis tree and one Eugenia Grandis tree in Singapore were analysed using computational fluid dynamics (CFD) modelling and validated with field measurements. For the numerical method, an innovative laser scanning approach was used to generate the tree geometries and to calculate the three-dimensional (3D) leaf area density distribution within the canopies. The canopies were represented by multiple porous domains and the turbulent effect of leaves was simulated by source and sink terms as a function of the calculated leaf area density. Computational fluid dynamics analyses using ANSYS 17.2 software were carried out on both leafless and leafed tree models. Three turbulent models, the Realizable k-ε model, Transition Shear Stress Transport model and Reynolds Stress Model were compared, and it was found that the differences in the drag forces among the turbulent models were negligible when they were meshed appropriately based on the grid independence study. The computed drag coefficient of the Khaya Senegalensis tree and the Eugenia Grandis tree from CFD modelling were similar within the range between 0.6 and 0.7. From field monitoring including the wind velocity and stem strains, the drag coefficients of both trees were calculated to be 0.51 and 0.40. Possible reasons causing the difference and limitations of the numerical method are discussed.